Effect of exercise alone and in combination with time-restricted eating on cognitive health in menopausal women - Beata Jóźwiak; Paweł Kleka; Ida Laudańska-Krzemińska (Frontiers in Public Health)
BackgroundCognitive complaints are commonly reported during menopause. Lifestyle interventions, such as exercise and time-restricted eating, are being investigated for their potential role in supporting cognitive health during menopause. This study investigated the effect of combining time-restricted eating (16:8) with a resistance and endurance circuit training program on cognitive health, as assessed using a comprehensive multi-domain cognitive test battery, in perimenopausal, menopausal, and postmenopausal women.MethodsFifty-nine perimenopausal, menopausal, and postmenopausal women were assigned into a combination group (exercise + time-restricted eating, n = 26) and into an exercise group (exercise only, n = 33). Assessments were performed before and after a 12-week period and included Stroop Test, N-back Test, assessment of BDNF and GDNF level, and EEG testing.ResultsReading interference tendency in Stroop Test improved significantly in the exercise group (p = 0.026) while there were no changes in the combination group. Working time in Stroop Test decreased significantly in both groups (p = 0.025 – exercise group; p = 0.032 – combination group). Resting-state theta activity (eyes closed) and N-back test-related brain activity increased significantly only in the exercise group (p = 0.043). There were no significant changes in naming interference tendency in Stroop Test, N-back test results, BDNF level and GDNF level in any group.ConclusionCombination of time-restricted eating and exercise does not result in superior improvements in cognitive health markers when compared with exercise alone in menopausal women. These results highlight the central role of physical exercise in maintaining cognitive health during menopause and suggest that adding time-restricted eating may not provide added value in this context. Future studies should investigate the underlying mechanisms through which multimodal lifestyle interventions may influence cognitive health in menopausal populations.Clinical trial registrationclinicaltrials.gov/study/NCT06138015, identifier NCT06138015.